The Application Of Group Investigation In Speaking Class At University of Nusantara PGRI Kediri - Jatmiko Jatmiko; Agung Wicaksono; Pamadya Vitasmoro (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2023)
Teaching is an interactive process, mostly involving classroom talk which takes place between teacher and students in certain definable activity. Speaking is one of the skills must be mastered by students as a foreign language. And teaching speaking is a process of giving help to the students to expressing their idea, taught, feeling, or practicing communication by using English. Teaching speaking is activity carried out by teachers and useful to train students to speak. Speaking is one tool to communicate with others people. Group Investigation is one of method that uses to learn speaking. The purpose of the research is (1) to describe the application group investigation (GI) in speaking class by an English lecturer, (2) to describe the students’ response to the application of group Investigation (GI). The research design applied in this research is descriptive qualitative research. The subject of this research is fourth semester students at English education department of UNP Kediri, consists of 22 students. The data used is questionnaire. This research is about the application of Group Investigation in speaking class. The teacher divided into small groups, choose sub-topic, investigation and discussion, and then presentation and evaluation. The result of questionnaire shows that 75% almost all of students answer strongly agree. It means that the application of group investigation in speaking class is very useful and helpful for the students to learn speaking. It can be concluded that the application of group investigation in speaking class was successful and it supports the theory.